COVID-19 in Solomon Islands - Economic and Social Impacts : Insights from the January-February 2022 Round of High Frequency Phone Surveys - World Bank (Washington, DC, 2022)
This report focuses on the socio-economic impacts of Coronavirus (COVID-19) in Solomon Islands. The fourth round of the high frequency phone survey (HFPS) interviewed 2,671 households in January-February 2022 on the socio-economic impacts of Coronavirus (COVID-19), including employment and income, community trust and security and COVID-19 vaccination. The January-February 2022 round occurred at the onset of the first wave of COVID-19.